Product Marketing: Building a Strong and Sustainable Brand - Ian Zulfikar (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze effective marketing strategies for building strong and sustainable brands amidst increasingly dynamic market competition. The research focuses on identifying key factors influencing brand awareness, consumer loyalty, and brand sustainability through an integrated marketing approach. The research method used is qualitative with a descriptive approach, involving literature review and interviews with marketing practitioners and consumers to gain an in-depth understanding of best practices in brand building. The results indicate that building a strong and sustainable brand requires an integrated and strategic marketing approach, focusing not only on product quality but also on a deep understanding of the target market, a clear brand identity, positive customer experiences, consistent communication, and the use of social media. Brand success is determined by a company's ability to adapt its products and marketing strategies to be relevant to consumer needs, differentiate the brand from competitors, build trust, and strengthen long-term loyalty. The study also highlights challenges faced, including intense competition, changing consumer preferences, the need for sustainable differentiation, and social and environmental responsibility.